Statistical Summary Of World Production And Trade Of Major Mineral Commodities For 1992 - Ivette E. Torres (The National Institute for Occupational Safety and Health (NIOSH), 1994)
The final 26 tables of this chapter, tables 24-49, extend and expand the statistical series on production that was started in the 1963 edition of the Area Reports: International volume of the Minerals Yearbook and that was subsequently updated and expanded in the 1965 and 1967-90 editions. Mainly because of the separation of the countries that formed the U.S.S.R., the column that provided a 5-year average, was deleted. The listing order of major producers, however, continued to be, as in past years, in descending order of rank in the year of review, 1992. This group of tables now includes each of the top 19 crude minerals in 1983 in terms of value of their output plus 3 others of lesser rank. These 22 crude mineral commodities accounted for more than 98 % of the estimated value of world crude mineral production in 1983. Coal production, included in the 1983 value of production table as two separated entries, is combined in one table in this chapter. World output of five key downstream products-aluminum, steel, cement, nitrogen in ammonia, and refined oil-is included because of their significance as products.